GLOBALNE POSTAWY STUDENTÓW LUBELSKICH WOBEC RELIGII - Kozak, Jarosław (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Sociologists of religion continue to emphasize unusual steadfastness of religion in Poland, also in its most general form – autodeclaration of faith and religious autoidentification. In the early phase of the system transformation after 1989, the domain of “national religiousness”, where faith of the nation functions more as a common rather than an individual value, was left almost untouched. Escalating secularization as well as structural individualisation make it legitimate to claim that symptoms of changes in the basic parameters of religious life among youth will gradually become more visible. The changes may include one’s affiliation to a particular faith or global attitude toward religion. Still, even in these environments, those changes will not have a revolutionary character.